Responding to COVID-19 in Urban Settings : Emerging Evidence, Lessons, and a Look Ahead - Ramana, Gandham N.V.; Mutasa, Ronald; Mohammed, Suresh Kunhi; Nandraj, Sunil; Jammy, Guru Rajesh; Smith, Owen (World Bank, Washington, DC, 2021)
Metropolitan areas drive economies, yet the same elements that contribute to economic growth, such as industrialization accompanied by migrant influx, result in overcrowding and poor housing and sanitation. These factors, coupled with intensive international connectivity, make cities extremely vulnerable to pandemics. Experiences from New York and São Paulo show that complex administrative structures; conflicting messages from federal, state, and city governments; human resource shortages; supply chain mismanagement; weak coordination between hospitals and public health systems; and poor linkages with the private sector are all limiting factors of a comprehensive pandemic response. COVID-19 has seriously impacted the delivery of essential health services, especially in cities, where the private sector and public hospitals deliver a significant share of primary care. COVID-19 also presents a major public mental health challenge both for health professionals and the public.